Representations : images of the world in Ciceronian oratory - Vasaly, Ann (University of California Press, 1993)
Ann Vasaly introduces representation theory into the study of Ciceronian persuasion and contends that an understanding of milieu--social, political, topographical--is crucial to understanding Ciceronian oratory. As a genre uniquely dependent on an immediate interaction between author and audience, ancient oratory becomes performance art. Vasaly investigates the way Cicero represented the contemporary physical world--places, topography, and monuments, both those seen and those merely mentioned--to his listeners and demonstrates how he used these representations to persuade. Her exceptionally well-written study deftly recaptures the immediacy of Cicero's oratory and makes a trenchant contribution to an important new area of inquiry in Classical Studies.